Inhibition of Histone H3K27 Acetylation Orchestrates Interleukin-9-Mediated and Plays an Anti-Inflammatory Role in Cisplatin-Induced Acute Kidney Injury - Jiang, Wenjuan; Yuan, Xinrong; Zhu, Hong; He, Changsheng; Ge, Caiqiong; Tang, Qing; Xu, Chuanting; Hu, Bingfeng; Huang, Cheng; Ma, Taotao (Frontiers in Immunology, 2020)
Nephrotoxicity is a major side-effect of cisplatin- and platinum-related chemotherapy, and inflammation contributes to disease pathogenesis. Interleukin-9 (IL-9) is a pleiotropic cytokine associated with inflammation. Here we investigated the key role of IL-9 as a regulator of protective mechanisms in cisplatin-induced acute kidney injury (AKI). We observed that IL-9 was decreased not only in a cisplatin-induced AKI mouse model but also in THP-1 and RAW264.7 cell lines. Seventy-two hours post-cisplatin injection, renal dysfunction and tubule injury were significantly attenuated in IL-9 overexpression adeno-associated virus (AAV9) treated mice. The levels of serum urea, serum creatinine, kidney injury molecule-1 (KIM-1) and histological damage were partially diminished following treatment with IL-9. The renoprotective effects of IL-9 may be attributed to the regulation of cytokines, and we found that IL-9 acted on macrophages in a regulatory manner, promoting an anti-inflammatory phenotype. Furthermore, IL-9 enhanced suppression of macrophage-driven renal inflammation. Inhibition of H3K27 acetylation orchestrated IL-9 mediated renoprotection in cisplatin-induced AKI. Thus, our findings indicate novel and potent anti-inflammatory properties of IL-9 that confer preservation of kidney function and structure in cisplatin-induced AKI, which may counteract kidney disease procession.